Bioelectrical impedance analysis for assessment of body composition in infants and young children‐A systematic literature review. Issue 3 (9th February 2021) - Lyons‐Reid, Jaz; Derraik, José G. B.; Ward, Leigh C.; Tint, Mya‐Thway; Kenealy, Timothy; Cutfield, Wayne S.
Summary: Bioelectrical impedance analysis (BIA) is an easy to use, portable tool, but the accuracy of the technique in infants and young children (<24 months) remains unclear. A systematic literature review was conducted to identify studies that have developed and validated BIA equations in this age group. MEDLINE, Scopus, EMBASE, and CENTRAL were searched for relevant literature published up until June 30, 2020, using terms related to bioelectrical impedance, body composition, and paediatrics. Two reviewers independently screened studies for eligibility, resulting in 15 studies that had developed and/or validated equations. Forty‐six equations were developed and 34 validations were conducted. Most equations were developed in young infants (≤6 months), whereas only seven were developed among older infants and children (6‐24 months). Most studies were identified as having a high risk of bias, and only a few included predominantly healthy children born at term. Using the best available evidence, BIA appears to predict body composition at least as well as other body composition tools; however, among younger infants BIA may provide little benefit over anthropometry‐based prediction equations. Currently, none of the available equations can be recommended for use in research or in clinical practice.